Factors Affecting Indonesian Pre-Service Teachers’ Use of m-LMS: A Mix Method Study - Aman, Aman; Prasojo, Lantip Diat; Sofwan, Muhammad; Mukminin, Amirul; Habibi, Akhmad; Yaqin, Lalu Nurul (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The purpose of this research is to investigate factors affecting Indonesian pre-service teachers’ (PSTs) teachers’ use of m-learning management systems (m-LMS) in higher education. The difference regarding the use of m-LMS based on some demographic information namely gender, university, year in university, and age are also reported as well as gaining an in-depth understanding of the use of m-LMS in Indonesian universities. To achieve this, two approaches, quantitative and qualitative, were applied. First, we developed and distributed a survey instrument to 210 students teachers based on the technology acceptance model (TAM). In addition, we interviewed 7 of the PSTs to obtain an in-depth understanding of the use of m-learning in their learning. Some statistical calculations were presented such as mean, standard deviation, Cronbach’s alpha, t-test, and ANOVA. Findings suggest that PSTs’ use m-LMS are related to their Perceived usefulness and perceived ease of use, Subjective norm and attitudes Self-efficacy and supporting condition. From these results, we recommend that teacher educators should target these factors within teacher development programs to prepare PSTs for successful use of m-LMS.